Lip Balm Daun Kelor Dan Daun Pandan Mengatasi Bibir Kering - Yenny Sri Handayani; Diajeng Olga Arulia Pining Kasih (Garina, 2022)
Lip Balm is one of the cosmetic products to moisturize the lips. The ingredients used in this lip balm are beeswax (beeswax), original olive oil, Moringa leaf powder and pandan leaf powder which are useful for dealing with dry lips because they contain vitamin C which has benefits for the lips. This lip balm has excellent receptivity and adds to the variety of lip balms by making use of natural ingredients. The purpose of this experiment is to find out and explain the process of making Lip Balm, to find out the benefits of Lip Balm, and to explain the advantages and disadvantages of Moringa Leaf and Pandan Leaf Lip Balm. The experiment of making Moringa Leaf and Pandan Leaf Lip Balm was carried out using the methods of observation, interviews, experiments, documentation, literature, and analysis. The composition of the lip balm is Moringa leaf powder 1gr, pandan leaf powder 1gr, beeswax 10gr, olive oil 6ml and this lip balm has a soft, dense and non-greasy texture. every day so that the lips are not dry and chapped. Based on sensory tests and public tests, this lip balm from Moringa leaves and pandan leaves is suitable for use because of its excellent benefits for moisturizing lips